2000
DOI: 10.1063/1.126931
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of misfit dislocations at interfaces of lattice-matched Ga0.5In0.5P/GaAs heterostructures

Abstract: A configuration of misfit dislocation dipoles is observed in a Ga 0.5 In 0.5 P heterostructure grown by solid-source molecular-beam epitaxy on GaAs. The dipole dislocations are mostly of 60°type, separated by ϳ3.5 nm. The dislocations are not produced by conventional lattice mismatch, rather, they could be the result of lateral compositional modulation in the Ga 0.5 In 0.5 P epilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…However, we did observe a special dislocation configuration -dislocation dipoles, along the GaInP-on-GaAs interface. 29 Dislocations are also observed inside the GaInP epilayers, as shown in Fig. 4.…”
Section: Discussionmentioning
confidence: 78%
“…However, we did observe a special dislocation configuration -dislocation dipoles, along the GaInP-on-GaAs interface. 29 Dislocations are also observed inside the GaInP epilayers, as shown in Fig. 4.…”
Section: Discussionmentioning
confidence: 78%
“…Another interesting result is that dislocation dipoles are also observed in some plastically relaxed dots, as shown in Figs. 4c and [27], who suggested that the dipole dislocations were formed due to the compositional modulation in the GaInP phase. In the dot case, the dislocation dipoles seem to have formed by a different mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, dislocations may play a role in the evolution of composition fluctuation (Cottrell, 1953;Léonard and Desai, 1998). Wang et al (2000Wang et al ( , 2001 reported that CM occurring in Ga 0.5 In 0.5 P/GaAs lattice-matched system generates misfit dislocation dipoles. When the stress due to CM reaches a certain critical value, dislocations tend to be introduced in order to relax the misfit strain.…”
Section: Introductionmentioning
confidence: 97%
“…They concluded that the dislocations are produced by lateral CM in the Ga 0.5 In 0.5 P epitaxial layer, but not by the conventional lattice mismatch. It is believed that the critical thickness for the formation of dislocations is reduced due to the CM (Wang et al, 2000(Wang et al, , 2001, which was first calculated by OvidÕko and Sheinerman (2002a,b). They assumed that the film and substrate materials are isotropic and CM occurs in a sinusoidal form and shows no variation through the entire film thickness (not in surface soft mode).…”
Section: Introductionmentioning
confidence: 99%